LITERARY FEATURES OF ENGLISH, UZBEK AND KARAKALPAK LULLABIES IN THE LITERATURE - Khojanova Nargul Jenisbayevna; T. Kerwenov (Journals Park Publishing, 2023)
The article is devoted to identification of the features of three languages such as Karakalpak- Uzbek and English, lullaby as a text of a complex semiotic nature and determination of typological features in the organization of an integral communicative space. It is postulated that the difference in sign is characteristic not only of modern texts, born of scientific and technological progress, which changed the sign nature of information, but also of a lullaby. It is noted that in linguistics, the study of a lullaby as a polycode text is not one of the intensively developed ones, and in English, Karakalpak and Uzbek languages, its linguistic understanding and description as a multilayered text is carried out for the first time, which determines the relevance of the work.
Keywords: lullabies, folklore, early stages of intrauterine, verbal layer, monotonous, lull babies to sleep.